(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present study aims to investigate the factors that influence the academic writing of Arab-Bedouin students as well as the personal factors and the academics who challenge them to succeed in acquiring higher education such as: Hebrew writing challenges as a second language, the variety of words and identity, the prestige of Hebrew and the tension between spoken and literary Arabic. It also examines whether writing in literary Arabic (their mother tongue) is more difficult than writing in Hebrew, which is considered a second language (Manor, 2016; Abu- Bakr, 2016). The research method is self-research which belongs to action research. This type of research develops in recent years and it deals with independent research on the work of teachers (Ferrance, 2000). This study is based on two methods: The first one is the writing product of students’ assignments in academic courses in the last two years in which there is writing in Arabic as well as in Hebrew. Thus, the writing products of students are collected in order to stand on their writing in both languages. After the collection phase, the researchers examine the types of deviations from Hebrew and Arabic standard language, the mutual effects of Hebrew and Arabic languages, the differences in the writing difficulties in both languages, and more. The second one examines the verbal expression of male and female students in presenting an article in Hebrew and Arabic. The study findings show that students’ difficulty in expressing themselves in literary Arabic orally is difficult than that in Hebrew. In other words, their ability to express themselves orally in Hebrew is better than that in Arabic. On the other hand, the study shows that the ability to write in literary Arabic is better than that in Hebrew. The findings show that the writing of Arab-Bedouin students contain errors that stem mainly from the sound similarity of the words, humanistic errors, morphology and the influences of Arabic - the mother tongue of Arab-Bedouin students. A more interesting finding from the current study shows that the ability of male students to express themselves in Hebrew is better than that of Bedouin female students, probably because of socio-cultural connections. The uniqueness of the study is that it is a pioneering study that comparatively examines the difficulties of Arab-Bedouin students in both Hebrew and Arabic in the academic world theoretically. Practically, it contributes greatly to academic difficulties that improve the level of writing and expression in both languages.